1995
DOI: 10.1037/0021-9010.80.1.168
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ratee task performance and interpersonal factors on supervisor and peer performance ratings.

Abstract: The study examines the effects of a wide array of rater-ratee relationship and rateecharacteristic variables on supervisor and peer job-performance ratings. Interpersonal ratings, job performance ratings, and ratee scores on ability, job knowledge, and technical proficiency were available for 493-631 first-tour U.S. Army soldiers. Results of supervisor and peer ratings-path models showed ratee ability, knowledge, and proficiency accounted for 13% of the variance in supervisor performance ratings and 7% for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
211
2
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(228 citation statements)
references
References 45 publications
(49 reference statements)
11
211
2
4
Order By: Relevance
“…Consistent with this, Borman, White, and Dorsey (1995) reported that likeability had little effect on task performance; LePine and Van Dyne (2001) showed no relationship between agreeableness and task performance on a laboratory task where performance was operationalized as decision making accuracy; and at least three meta-analyses have failed to show a consistent relationship between agreeableness and task performance (Hough et al, 1990;Hurtz & Donovan, 2002;Salgado, 1997). Commenting on these findings, Johnson (2003) noted that agreeableness may predict task performance in some jobs but not in others.…”
Section: Personality Task Performance and Helpingmentioning
confidence: 97%
“…Consistent with this, Borman, White, and Dorsey (1995) reported that likeability had little effect on task performance; LePine and Van Dyne (2001) showed no relationship between agreeableness and task performance on a laboratory task where performance was operationalized as decision making accuracy; and at least three meta-analyses have failed to show a consistent relationship between agreeableness and task performance (Hough et al, 1990;Hurtz & Donovan, 2002;Salgado, 1997). Commenting on these findings, Johnson (2003) noted that agreeableness may predict task performance in some jobs but not in others.…”
Section: Personality Task Performance and Helpingmentioning
confidence: 97%
“…Borman, White, Pulakos, and Oppler (1991) found that high dependability among military personnel led to fewer disciplinary infractions and higher performance ratings. Borman, White, and Dorsey (1995) also reported a strong relationship between dependability and both peer and supervisor performance ratings. Hough (1992) found that dependability was related to ratings of teamwork, and Barrick, Stewart, Neubert, and Mount (1998) found that work teams with higher levels of conscientiousness (broadly defined) received higher ratings of team performance.…”
Section: Conscientiousnessmentioning
confidence: 99%
“…Hough (1992) found that dependability was related to ratings of teamwork, and Barrick, Stewart, Neubert, and Mount (1998) found that work teams with higher levels of conscientiousness (broadly defined) received higher ratings of team performance. Behavioral markers of dependability reported by peers and supervisors in Borman et al (1995) include "Count on for back up" and "Trust and depend on." Thus, team members high on dependability are likely to be more responsible and can be relied on to back up other team members.…”
Section: Conscientiousnessmentioning
confidence: 99%
“…Work samples have also been held in high regard as criterion measures (Borman, White, & Dorsey, 1995;Kavanagh, Borman, Hedge, & Gould, 1987). For example, Borman and Hallum (1991) noted that"...some researchers have maintained that work samples.. .are the highest fidelity performance-measurement method available and that they provide the most valid indication of 'actual' performance" (p. 11).…”
Section: Charles E Lancementioning
confidence: 99%
“…Granted, work sample performance measures are high fidelity measures of "can-do" aspects of job performance (versus "will-do" aspects, see Borman et al, 1995;Borman, White, Pulakos, & Oppler, 1991;DuBois, Sackett, Zedeck, & Fogli, 1993;Motowidlo, Borman & Schmit, 1997;Motowidlo & VanScotter, 1994;Sackett, Zedeck, & Fogli, 1988). However, they are not without their limitations.…”
Section: Charles E Lancementioning
confidence: 99%